Examining Life in Truko Village in the Differences in Traditions Between Nahdlatul Ulama and Muhammadiyah - Muhammad Zuman Firjatullah; Tegar Arief setyawan; Maulani Maulani; Saydimas Umitdhavala; Ariska Kurnia Rachmawati (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Indonesia is a country with a diversity of ethnicities, religions, races and cultures. This diversity underlines the importance of Indonesian unity, which is contained in the third principle of Pancasila. In achieving this unity, heterogeneous Indonesian people must get along well, understand each other, respect each other and accept and appreciate differences. In this study, we used desk research-type literature to collect data from reliable sources, prioritizing literature search over other functions. This research strategy uses qualitative methods so that the data collected from the study findings can be conveyed in words. The diversity of religious communities is spread in various parts of Java, including in Truko Village, Kangkung Subdistrict, Kendal Regency. In Truko village there are various Islamic organizations such as Nahdhatul Ulama (NU), Muhammadiyah, Persis, and LDII, with the majority having a Nahdlatul Ulama background which is synonymous with traditional Islam. Polaman hamlet, Truko Village, Kangkung Subdistrict, Kendal Regency becomes an interesting thing about religious tolerance because in this hamlet NU and Muhammadiyah followers live in a harmonious atmosphere, and even harmony is also shown by Muslims and Javanese Christians. Adherents of Nahdlatul Ulama and Muhammadiyah can actually work together and do not see the different status of the religion they adhere to.